Evaluation of strategic stockpoints for UNFPA using a facility location mode - Hansson,Erik; Sagar,Dayanand (2018)
Distribution and warehousing networks of Humanitarian Organizations has proven to be an area where cost reductions and shortened lead times can be achieved. Humanitarian organizations have also started pre-positioning goods in anticipation of disasters as a way to improve their disaster preparedness. Research in the area has, generally, been extensive but few articles have tried to incorporate the shelf life of the goods that have been prepositioned. The study aims at incorporating the lessons learned from research of prepositioning and network layouts for humanitarian organizations with the shelf life aspects. To achieve the purpose of this study, a literature review and a single case study combined with mathematical modelling. The case chosen was a humanitarian organization with products that has shelf life restrictions: UNFPA. The subjects of the literature review covered case-specific factors regarding network planning, disaster preparedness and facility location problems in both commercial and humanitarian organizations. 13 interviews and two validation meetings were carried out to lay the ground for the understanding of UNFPA as well the need that should be fulfilled by a facility location model. When these two steps had been completed a new facility location model was developed that incorporated a global demand for UNFPA, 14 potential warehouse locations, transport and purchasing costs, shelf life limitations and relevant factors such as logistics hardship. The model was run in an optimization program to be able to give recommendations as to how UNFPA may revise their current layout. The study identified some clear benefits as well as drawbacks with the pre-positioning of goods on both a regional and national level. The study also identified some core issues for UNFPA that would have to be solved before an alteration of the warehouse network could be carried out. The study did, however, show that there would be clear cost reduction benefits from switching to a decentralized warehouse layout as well as some lead time reductions. The optimization model that was developed is also applicable in another case with a Humanitarian Organization using perishable commodities.
Keywords: Humanitarian Logistics; Facility Location; UNFPA; Perishable Commodities; Pre-positioning